FORMULASI MODEL KADAR KOLESTEROL SERUM MELALUI PENDEKATAN UKURAN SKINFOLD PADA ORANG DEWASA - Ila Fadila (Jurnal Matematika Sains dan Teknologi, 2006)
The study was conducted to explore the relationship between anthropometric measurement, i.e. skinfold thickness and cholesterol consentration in adult male and female blood. Other variables assumed as confounders including respondent characters namely: age, sex, ethnic, smoking habit, and activity. Analysis was done to a data from Health and Nutrition Survey on Adult on six cities in Indonesia. Prediction model of serum cholesterol with nutritional status assessment was developed by multiple regression analysis. Backward elimination procedure was used for model processing. The study result indicated that there was positive correlation between cholesterol and skinfold, age, and ethnic. Prediction model of serum cholesterol can be showed: Serum Cholesterol = 153,58 + 0,36 Skinfold + 0,34 age – 1,46 Sex – 48,71 Activity + 27,84 Ethnic